How to be an alien - Hites, Sándor (Primerjalna književnost, 2017)
The paper examines the best-selling satirical book How to Be an Alien (1946) by the Hungarian émigré journalist and prominent British humorist George Mikes (1912-1987). I argue that tackling the issues of emigration, integration and belonging, Mikes employs a mock-anthropological approach: ironically reworking the notions of observation and imitation as survival strategies, HTBA grasps the absurdities underlying both British life and the newcomer's struggle to blend in. The two sequels Mikes wrote to HTBA decades later demonstrate that once the "alien" has been successfully integrated, the sense of acquired Britishness only produces further absurdities. Examining HTBA and a selection of his other works, I also claim that Mikes's satire is an unacknowledged contribution to the modern philosophical tradition of "strangeness" (exemplified by authors ranging from G. Simmel to H. Arendt, Th. Adorno and Z. Bauman). Today, Mikes's legacy continues to inspire expatriates living in London and elsewhere. However, his emblematic work has also inspired a stream of books with diametrically opposite intentions: these encourage their native readers to regain their allegedly fading socio-cultural heritage. In the transformation of Mikes's satire about aliens adapting to new environments into an encouragement of natives to embrace their own, one can witness both the disintegration of traditional cultural belonging and a new appeal of indigeneity.
Keywords: "How to be an alien"; angleška književnost; Eastern Europe; emigracija; emigration; English literature; Hungary; intelektualci; intellectuals; Madžarska; Mikes, George, 1912-1987; nacionalni stereotipi; national stereotypes; satira; satire; strangeness; tujost; Vzhodna Evropa